Possible Serological Markers to Predict Mortality in Acute Exacerbation of Idiopathic Pulmonary Fibrosis - Yoshimasa Hachisu; Keisuke Murata; Kousuke Takei; Takuma Tsuchiya; Hiroaki Tsurumaki; Yasuhiko Koga; Takeo Horie; Atsushi Takise; Takeshi Hisada (Medicina, 2019)
Background and objectives: Idiopathic pulmonary fibrosis (IPF) has a particularly poor prognosis, and most IPF-related deaths are due to acute exacerbation (AE) of this condition. Few reports about biomarkers to predict prognosis of AE-IPF have been published since the release of the new AE-IPF criteria in 2016. The present study investigated relationships between serological markers and in-hospital mortality after the onset of AE-IPF. Methods: Demographic, serological, and imaging data from patients hospitalized at the Maebashi Red Cross Hospital (Gunma, Japan) between 1 January 2013, and 31 December 2017, were retrospectively reviewed. Subjects fulfilling the diagnostic criteria for AE-IPF were divided into those who survived or died; statistical analysis of risk factors was performed using data from these two groups. Results: Diagnostic criteria for AE-IPF were fulfilled by 84 patients (59 males (70.2%)), with a median age of 78 years (range, 56–95 years). IPF was diagnosed before hospitalization in 50 (59.5%) patients and 38 (45.2%) died in hospital. Among the serological markers at hospitalization in the deceased group, C-reactive protein (CRP) was significantly higher than in the survivor group (p = 0.002), while total serum protein (p = 0.031), albumin (p = 0.047) and total cholesterol (p = 0.039) were significantly lower. Cox hazard analysis of factors predicting mortality, corrected for age, sex and BMI, revealed the following: CRP (hazard ratio (HR) 1.080 (95% confidence interval (CI) 1.022–1.141); p = 0.006), LDH (HR 1.003 (95% CI 1.000–1.006); p = 0.037), and total cholesterol (HR 0.985 (95% CI 0.972–0.997); p = 0.018). Conclusions: Our data suggest that CRP, LDH, and total cholesterol may be biomarkers predicting mortality in patients with AE-IPF. However, only prospective controlled studies can confirm or not our observation as a generalizable one.